Head-Mounted Display Virtual Reality in Post-secondary Education and Skill Training - Concannon, Brendan J.; Esmail, Shaniff; Roduta Roberts, Mary (Frontiers in Education, 2019)
Background: This review focused on how immersive head-mounted display virtual reality (VR) was used in post-secondary level education and skill training, with the aim to better understand its state of the art as found from the literature. While numerous studies describe the use of immersive VR within a specific educational setting, they are often standalone events not fully detailed regarding their curricular integration. This review aims to analyse these events, with a focus on immersive VR’s incorporation into post-secondary education. Objectives: O1) Review the existing literature on the use of immersive VR in post-secondary settings, determining where and how it has been used within each educational discipline. This criterion focused on literature featuring the use of immersive VR, due to its influence on a user’s perceived levels of presence and imagination. O2) Identify favourable outcomes from the use of immersive VR when compared to other learning methods. O3) Determine the conceptual rationale (purpose) for each implementation of immersive VR as found throughout the literature. O4) Identify learning theories and recommendations for the utilization of immersive VR in post-secondary education. Methods: A literature review was undertaken with searches of Education Research Complete, ERIC, MEDLINE, EMBASE, IEEE Xplore, Scopus and Web of Science: Core Collection to locate reports on the use of immersive VR in post-secondary curricula. Results: 119 articles were identified, featuring disciplines across Arts and Humanities, Health Sciences, Military and Aerospace, Science and Technology. 35 out of 38 experiments reported to have found a positive outcome for immersive VR, after being compared with a non-immersive platform. Each simulation’s purpose included one or more of the following designations: skill training, convenience, engagement, safety, highlighting, interactivity, team building and suggestion. Recommendations for immersive VR in post-secondary education emphasize experiential learning and social constructivist approaches, including student-created virtual environments that are mainly led by the students themselves under team collaboration. Conclusion: Immersive VR brings convenient, engaging and interactive alternatives to traditional classroom settings as well as offers additional capability over traditional methods. There is a diverse assortment of educational disciplines that have each attempted to harness the power of this technological medium.